Strategi Meningkatkan Daya Saing Pasar Tradisional (Kasus Revitalisasi Pasar Tradisional di Kota Banjarmasin) - Farid Zaky Yopiannor (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to: (1) Analyze consumers' assessment of traditional markets on the policy to revitalize traditional markets in the city of Banjarmasin, (2) Determine the assessment of the management and traders of traditional markets afterthe revitalization policies are conducted by the Government of Banjarmasin, (3) Identify the internal and external factors affecting the traditional markets in an effort to improve the competitiveness of traditional markets in the city of Banjarmasin, (4) To formulate the strategy options for improving the competitiveness of traditional markets in the city of Banjarmasin, (5) To formulate strategic priorities in an effort to improve the competitiveness of traditional markets in Banjarmasin.The results show that: (1) the performance of traditional markets in the city of Banjarmasin because the revitalization policy is not optimal; this is proven by the consumers' assessment of the marketing mix variables (marketing mix) 7P which is still low on some attributes, such as product quality factors, promotional products market traditional, traditional market traders and service, (2) the traditional-market revitalization in Banjarmasin is not optimum because it is still limited to procedural and has not touchedthe substantive aspects concerning the increased competitiveness of traditional markets, (3) the priority strategy to enhance the competitiveness of traditional markets are (a) optimizing the arrangement of traders with neat and orderly zoning systems (clusters); (b) optimizing the publication and promotional traditional-market activities post revitalization policies; (c) establishing cooperation with universities through R & D (Research and Development) of traditional markets.It is suggested that revitalization of traditional markets in the city of Banjarmasin must be comprehensive, focusing on the aspects of business management of professionalmarketing and empowerment of traditional market traders